A comparative in vitro and in vivo analysis of the impact of copper substitution on the cytocompatibility, osteogenic, and angiogenic properties of a borosilicate bioactive glass - Fiehn, Linn Anna; Kunisch, Elke; Saur, Merve; Arango Ospina, Marcela; Merle, Christian; Hagmann, Sébastien; Stiller, Adrian; Hupa, Leena; Kaňková, Hana; Galusková, Dagmar; Renkawitz, Tobias; Boccaccini, Aldo R.; et al. (Journal of Biomedical Materials Research Part A, 2024)
The 0106-B1-bioactive glass (BG) composition (in wt %: 37.5 SiO2, 22.6 CaO, 5.9 Na2O, 4.0 P2O5, 12.0 K2O, 5.5 MgO, and 12.5 B2O3) has demonstrated favorable processing properties and promising bone regeneration potential. The present study aimed to evaluate the biological effects of the incorporation of highly pro-angiogenic copper (Cu) in 0106-B1-BG in vitro using human bone marrow-derived mesenchymal stromal cells (BMSCs) as well as its in vivo potential for bone regeneration. CuO was added to 0106-B1-BG in exchange for CaO, resulting in Cu-doped BG compositions containing 1.0, 2.5 and 5.0 wt % CuO (composition in wt %: 37.5 SiO2, 21.6/ 20.1/17.6 CaO, 5.9 Na2O, 4.0 P2O5, 12.0 K2O, 5.5 MgO, 12.5 B2O3, and 1.0/ 2.5/ 5.0 CuO). In vitro, the BGs' impact on the viability, proliferation, and growth patterns of BMSCs was evaluated. Analyses of protein secretion, matrix formation, and gene expression were used for the assessment of the BGs' influence on BMSCs regarding osteogenic differentiation and angiogenic stimulation. The presence of Cu improved cytocompatibility, osteogenic differentiation, and angiogenic response when compared with unmodified 0106-B1-BG in vitro. In vivo, a critical-size femoral defect in rats was filled with scaffolds made from BGs. Bone regeneration was evaluated by micro-computed tomography. Histological analysis was performed to assess bone maturation and angiogenesis. In vivo effects regarding defect closure, presence of osteoclastic cells or vascular structures in the defect were not significantly changed by the addition of Cu compared with undoped 0106-B1-BG scaffolds. Hence, while the in vitro properties of the 0106-B1-BG were significantly improved by the incorporation of Cu, further evaluation of the BG composition is necessary to transfer these effects to an in vivo setting.
CRIS-Team Scopus Importer:2024-05-03
Keywords: angiogenesis; bioactive glass; bone defect regeneration; boron; copper; mesenchymal stromal cells; osteogenesis